A comparison of fallout 236U and 239Pu uptake by Australian vegetation. (January 2016) - Froehlich, M.B.; Dietze, M.M.A.; Tims, S.G.; Fifield, L.K.
Abstract: The isotopes 236 U and 239 Pu, both produced during nuclear weapons tests carried out in the 1950s and 1960s, are present in the environment and may be used as tracers for soil erosion studies. Although these radionuclides occur only at ultra-trace levels in nature, they can be readily measured by accelerator mass spectrometry with the 14UD heavy ion accelerator at the Australian National University. We have analysed a series of vegetation samples for their 236 U and 239 Pu concentration and compared the results with those found in the surrounding soil. 236 U could be measured in all collected samples whereas 239 Pu could not be detected in several vegetation samples due to its very low concentration, although it was readily detectable in the soil. We find that, relative to plutonium, 236 U is preferentially taken up by plants with enrichment factors ( 236 U/ 239 Pu)veg /( 236 U/ 239 Pu)soil that range between 7 and 52 in the present study. Highlights: We have analysed and compared concentrations of fallout isotopes 236 U and 239 Pu in vegetation samples and nearby soils. The 236 U concentration could be readily detected in all vegetation samples whereas 239 Pu only in 2/3 of the sampling set. In soil the 236 U and 239 Pu concentrations are significantly higher than in the vegetation. Our findings suggest a higher 236 U uptake by plants than 239 Pu although Pu is more elevated in soil.